Analysis of Microstrip Line Fed Patch Antenna for Wireless Communications - Singh Ashish; Aneesh Mohammad; Kamakshi; Ansari J. A. (Open Engineering, 2017)
In this paper, theoretical analysis of microstrip line fed rectangular patch antenna loaded with parasitic element and split-ring resonator is presented. The proposed antenna shows that the dualband operation depends on gap between parasitic element, split-ring resonator, length and width of microstrip line. It is found that antenna resonates at two distinct resonating modes i.e., 0.9 GHz and 1.8 GHz for lower and upper resonance frequencies respectively. The antenna shows dual frequency nature with frequency ratio 2.0. The characteristics of microstrip line fed rectangular patch antenna loaded with parasitic element and split-ring resonator antenna is compared with other prototype microstrip line fed antennas. Further, the theoretical results are compared with simulated and reported experimental results, they are in close agreement.